Synthesis, characterization, CT‐DNA binding and docking studies of novel selenated ligands and their palladium complexes. (10th March 2020) - Prabhu Kumar, K.M.; Vasantha Kumar, B.C.; Kumar, P. Raghavendra; Butcher, Ray J.; Vivek, H.K.; Suchetan, P.A.; Revanasiddappa, H.D.; Foro, Sabine
Abstract : A novel selenated Schiff base ( S )‐L 1 H has been synthesized from (2 S )‐1‐(benzylselanyl)‐3‐phenylpropan‐2‐amine which upon reduction formed a reduced Schiff base ( S )‐L 2 H . Palladium (II) complexes ( S )‐1 and ( S )‐2 of ligands ( S )‐L 1 H and ( S )‐L 2 H respectively were successfully synthesized. The structures of all four compounds were thoroughly identified by analytical and various spectroscopic techniques. The absolute molecular structures of the above two complexes were further confirmed by single crystal X‐ray diffraction. Both ( S )‐L 1 H and ( S )‐L 2 H coordinated as monobasic (( S )‐L 1–2 ), chelating, tridentate (Se, N, O − ) ligands resulting in the complexes of composition ( S )‐ [PdCl(L 1/2 )] [( S )‐1/2 ]. In the crystals of complexes ( S )‐1 and ( S )‐2, there were moderate to strong Se⋯O, CH⋯Cl and CH⋯O types of intermolecular secondary interactions. CT‐DNA binding activity of these selenium‐containing ligands and their palladium complexes bearing a Pd–Se bond have been evaluated for the first time by performing electronic absorption titration and fluorescence emission quenching using CT‐DNA‐EB and viscometric experiments. These ligands and complexes exhibited remarkable DNA binding activity as shown by their intrinsic DNA binding constants ( K b ) and Stern–Volmer constants ( K sv ) in the ranges 5.2–9.9 × 10 4 and 3.6–4.7 × 10 4, respectively. The viscosity of CT‐DNA decreases with increasing concentration of these compounds. The results of the DNA‐binding studies revealed that all of the compounds interact with DNA at a minor groove which was further confirmed by molecular docking studies. Abstract : Synthesized chiral selenated ligands and their palladium complexes. The absolute crystal structures of palladium complexes determined by single crystal X‐ray diffraction. The new ligands and complexes were explored for CT‐DNA binding and docking studies.